SEM/EDX AND XRD CHARACTERIZATION OF SILVER NANOCRYSTALLINE THIN FILM PREPARED FROM ORGANOMETALLIC SOLUTION PRECURSOR - Dimitrijević, Radovan Ž.; Cvetković, Olga G.; Miodragović, Zoran M.; Simić, Miloš B.; Manojlović, Dragan D.; Jović, Vesna B. (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
The Ag nano-structured thin films prepared on flat glass substrates have been studied. The ball-like silver nanoparticles have been synthesized in large quantity by using a modified method of hydrolytic decomposition of silver complexes with amino types ligands formed in ethanol aqueous solution. SEM properties show that Ag nanoparticles are all sphere shaped with bimodal size (40 and 70 nm) distribution. The results of XRD powder pattern examination show that Ag nanoparticles are pure phase, well crystallized. The unit cell dimensions measured on synthesized Ag nano films show small but frequent contraction in comparison to Ag metal standard.